The moderating effect of employee relations on networking towards workplace happiness among married women in Malaysia - Wok, Saodah; Hashim, Junaidah (Elsevier, 2015)
This study tries to examine the moderating effect of employee relations in enhancing the workplace happiness. A social exchange theory was used. A total of 1200 married working women in the public, private and government-linked organizations in Kuala Lumpur, Malaysia were sampled using a stratified random sample. The study employed a survey method, using questionnaire as the research instrument to collect data. Results showed that there is a strong positive relationship between internal contacts and workplace happiness while the relationship between external contacts is moderately positive. All the hypotheses are supported.